Jewish portraits, Indian frames : women's narratives from a diaspora of hope - Silliman, Jael Miriam (Brandeis series on Jewish women, 2001)
"Jewish Portraits, Indian Frames offers a personal and social history of the author's great-grandmother, grandmother, and mother - Baghdadi Jews who lived most of their lives in the Jewish community in Calcutta. Silliman begins with a portrait of Farha, her maternal great-grandmother, who dwelled almost entirely within the Baghdadi Jewish community no matter where she and her husband travelled on business (Calcutta, Rangoon, Singapore).